Approach to eliasian and bourdieusian concepts: analysis model in Physical Education research (Research, Society and Development, 2022)
This theoretical essay aims to approach the Eliasian and Bourdieusian concepts, even bearing in mind that a depth is uncertain, since synthesizing Elias and Bourdieu in a single essay is, at least, improbable. The basic principles of “procedural sociology”, the relationship between “sociogenesis” and “psychogenesis” and the concepts of “second nature”, “configuration” and “webs of interdependence” in Norbert Elias' work are revisited. While in Pierre Bourdieu's “symbolic sociology”, the concepts of “social fields”; the “capital” principles; the ​​“habitus” idea; and the “reproduction theory” are highlighted. Thus, in addition to contribute to the body of knowledge, either in relation to scientific literacy in the great area of ​​Health Sciences, or in relation to the paradigmatic restructuring of research on Physical Education regarding the school educational action, in particular, the approach comes to cooperate with the proposal to bring together different areas of knowledge (Philosophy, Sociology, History, Psychology). It should be noted that Physical Education itself, as it is considered a practice of immediate social intervention, lacks (still) theoretical-methodological assumptions capable to define its own analysis model regarding scientific research.